1981
DOI: 10.3168/jds.s0022-0302(81)82709-9
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nutrition and Management of Calves and Heifers

Abstract: Strides have been significant in the knowledge of calf and heifer rearing during the last 25 yr. Much information has been gathered on digestive enzymes, development of the digestive system, and metabolism. Investigations have clarified further the role of colostrum in immunity and nutrition of the young calf. Several sources of nutrients have been tested for their suitability in formulation of acceptable milk replacers and calf starters. Once-a-day feeding of milk, colostrum, or milk replacer and early weanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
6

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 50 publications
1
18
0
6
Order By: Relevance
“…Similar pathological changes associated with soy feeding in milk replacers were reported by several authors (Colvin and Ramsey, 1968;Coblenz et al, 1976;Otteby and Linn, 1981).…”
supporting
confidence: 66%
“…Similar pathological changes associated with soy feeding in milk replacers were reported by several authors (Colvin and Ramsey, 1968;Coblenz et al, 1976;Otteby and Linn, 1981).…”
supporting
confidence: 66%
“…Vazques-Anon et al (1993a) reported a similar increase to pH 6.0 by 17 weeks of age, which is closer to the optimum for microbial proteolysis. The increase may be due to increased absorption of VFA as the rumen matures (Otterby & Linn, 1981), or to increased salivary secretion (Anderson et al, 1987b).…”
Section: Figure 3 Rumen Volatile Fatty Acid Concentrations From 8 To mentioning
confidence: 99%
“…This would have adverse effects on the dairy farmer and, eventually, the consumers ofdairy products. Furthermore, the gene frequency may not be as small (<1%) as it appears in the herd studied, raising the possibility that UMP synthase deficiency may already be responsible for unexplained cases of herd-specific high calf mortality (17). In addition, the errors of metabolism due to the homozygous condition could contribute to postconception embryonic and fetal deaths that lead to decreased fertility (18).…”
Section: Resultsmentioning
confidence: 94%